SHADOWING - Ahmedova Mahliyo; Nodirbekov Davron (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Shadowing is the right method to use when you want to observe an individual and document observations in “as it was happening” format. This method is devoid of probing and you would use this when you don’t want to come in the way of the participant and his natural behaviour.